Geografia do hip hop na Grande Vitória-ES : o lugar em tempos de globalização - Torreão, Rafael Sapiência (2014)
The discussion of the place in times of globalization is the subject of this work, which focuses in the configuration of the Hip Hop movement in the metropolitan area of Grande Vitória (RMGV) within the process inherent to the intensification of globalized relations. The main objective is to indetify the specificities of the local Hip Hop - as a popular contemporary expression - in its relation to the geographical dimension, seen here through the inseparability of object and action systems. To this end, the discussion references based on theoretical literature studies of globalization and its social, cultural and political impacts, and other works, both in a geographical perspective and related areas. Rescues the actions of the protagonists throughout the period extending from 1980 to 2005, through interviews and visits to specialized journals. The results allow to identify three moments of the local Hip Hop, ranging from the prevalence of the practice of street dance (break) in some places of the city, through politicization and consolidation of the four elements (Dj, Mc, Graffiti and Break) until times characterized by the appropriation of technical and informational possibilities.